MAXIMIZING PROFITABILITY: ANALYZING THE IMPACT OF OPERATIONAL EFFICIENCY AND CAPITAL STRENGTH ON BANK BJB SYARIAH'S FINANCIAL PERFORMANCE - Siregar, Rahmi Annasari; Arif, Suyud; Kartika, Tika (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2024)
This study aims to analyse the impact of the BOPO (Operating Costs to Operational Income) and CAR (Capital Adequacy Ratio) ratios on the profitability of Islamic banks registered with the OJK for the period from 2015 to 2022. Using the Vector Auto Regression (VAR) method, the research employs purposive sampling to select relevant data. The findings reveal that, for Bank BJB Syariah, the BOPO ratio does not have a significant effect on profitability, as indicated by a probability value of 0.2047, which exceeds the 10% significance level. Similarly, the CAR ratio also shows no significant impact on profitability, with a probability value of 0.9785, again above the 10% threshold. These results suggest that, within the context of Bank BJB Syariah, both operational efficiency and capital adequacy do not directly influence profitability as measured by Return on Assets (ROA). This study contributes to the understanding of the financial dynamics of Islamic banking, highlighting the need for further investigation into other factors that may affect profitability in this sector.